Marine mussel-based biomarkers as risk indicators to assess oceanic region-specific microplastics impact potential - Chi-Yun Chen (Elsevier, 2021)
Microplastics (MPs) pollution in the ocean is an area of growing concern. Marine fauna subject to MPs exposure from various environmental sources are most likely to have detrimental effects on their immune system. However, studies of potential risks of MPs on marine ecosystems in light of environmental concentrations are largely limited. To this end, we presented an approach for assessing potential impact of MPs on marine ecosystems based on marine mussel Mytilus-based probabilistic risk assessment framework. The immunotoxic-based biomarkers of Mytilus were used to assess the impact of MPs on marine environment appraised with datasets by compiling oceanic region-specific and comprehensive MPs−environment studies along with published toxicity experiments. The immunological effects of MPs on lysosomal destabilization and phagocytosis in hemocytes of Mytilus were reconstructed as the concentration–response functions. We assessed the risk for marine environment exceeding a threshold of Mytilus-based immunological toxicity based on the benchmark concentration (BMC) approach corresponding to a 10% inhibition effect (BMC10). We estimated BMC10 values for inhibitions of lysosomal membrane stability and phagocytosis to be 1.4 and 0.4 mg L−1, respectively. Here we showed that the overall MPs-associated impact potential was low among South Pacific Ocean, Mediterranean Sea, and South Atlantic Ocean. However, we found that MPs from North Pacific Ocean were very likely (>90% probability) to pose a potential threat to marine mussels. Our findings have important implications for understanding the linked relationships between environmental MPs and likelihood of exposure risk for marine organisms in different oceanic regions around the world. We suggest that Mytilus-based risk indicator for estimating risk metrics of essential marine ecosystems posed by environmentally relevant MPs concentrations can help inform practices for the sustainable management and for mitigating the environmental MPs-induced negative impact on marine organisms.